PANELIST RESPONSE OF PASTEURIZED FRESH MILK FORTIFIED EXTRACT YELLOW SWEET POTATO - S. W., WITAWAN; LINDAWATI, S. A.; MIWADA, I N. S. (Majalah Ilmiah Peternakan, 2021)
This study aims to determine the response of the panelists after pasteurization of fresh cow’s milk fortified with yellow sweet potato extract through sensory testing. The research was conducted from June to August 2020 at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University. The experimental design used was a Complete RandomIzed Design (RAL) with four treatments and four repeats namely fortification of 0% yellow sweet potato extract (P0), fortification of 5% yellow sweet potato extract (P1), fortification of 10% yellow sweet potato extract (P2), fortification of 15% yellow sweet potato extract (P3). These variables observed included color, aroma, taste, viscosity, overall acceptance, and pH. The results of the research on pH test and panelist responses to taste, viscosity, and overall acceptance of fresh cow’s milk fortified with yellow sweet potato in each treatment showed no significant differences (P>0.05) but the color and aroma showed signifi- cant differences (P<0.05). The conclusion of this study is that the response of the panelists to fresh post-pasteurized cow’s milk fortified with yellow sweet potato extract gives a yellowish color and sweet potato aroma. Panelists gave a favorable response to fresh post-pasteurized cow’s milk fortified with 5% yellow sweet potato extract and a pH value according to Indonesian National Standard (SNI).